Single Variable Calculus - Stewart, James (Australia Thomson Brooks, 2009)
James Stewart continues to set the standard for the course while adding new diagnostic tools, carefully revised content, and all-new course management tools build on the foundation of his renowned content.
Include Appendices and Index.
Metric International Version.
Keywords: Calculus -- Variables (Mathematics) -- Calculus--Study and teaching (Secondary) -- Differential calculus